ANALYSIS OF THE ABILITY TO WRITE NASKHI SCRIPT AMONG SIXTH GRADE STUDENTS AT AL IHSAN ISLAMIC SCHOOL MEDAN - Cut Mayang Ramadhani; Kamalia Kamalia; Syaukani Syaukani (Universitas Islam Negeri Sumatera Utara Medan, 2025)
This study investigates the writing proficiency of sixth-grade students at Madrasah Al Ihsan Medan in producing Khat Naskhi script, which remains insufficiently neat and does not fully conform to the proper conventions of Arabic calligraphy. The study aims to (1) describe the students' level of competence in writing Khat Naskhi, (2) identify common errors and weaknesses found in their writing, and (3) analyze the internal and external factors influencing their performance. A descriptive qualitative method was employed, adopting Miles and Huberman's analytical model, which comprises three major stages: data reduction, data display, and conclusion drawing/verification. Data were collected through observation, interviews, and documentation involving one teacher and fifteen sixth-grade students at Madrasah Al Ihsan Medan. The findings reveal that the students' ability to write Khat Naskhi during Al Khat lessons remains below the expected standard. Several factors contribute to this condition, including insufficient learning materials, lack of practice outside classroom hours, low student engagement during lessons, and limited instructional time for Al Khat subjects. The study underscores the need for enhanced pedagogical support, increased practice opportunities, and curriculum adjustments to improve students' mastery of Khat Naskhi.